2022
DOI: 10.1002/jcsm.13110
|View full text |Cite
|
Sign up to set email alerts
|

Grip strength is inversely associated with DNA methylation age acceleration

Abstract: Background There is a large body of evidence linking muscular weakness, as determined by low grip strength, to a host of negative ageing-related health outcomes. Given these links, grip strength has been labelled a 'biomarker of aging'; and yet, the pathways connecting grip strength to negative health consequences are unclear. The objective of this study was to determine whether grip strength was associated with measures of DNA methylation (DNAm) age acceleration. Methods Middle age and older adults from the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Lower mDNAge in muscle appears to be a feature of the molecular environment with exercise adaptation that could have practical consequences for biological ageing and muscle performance. Indeed, emerging evidence suggests that blood mDNAge inversely associates with grip strength and frailty in ageing humans (Peterson et al., 2022; Verschoor et al., 2021) and is lower following a dietary/physical activity intervention in postmenopausal women (Fiorito et al., 2021). Exercise training and OKSM share substantial gene expression overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Lower mDNAge in muscle appears to be a feature of the molecular environment with exercise adaptation that could have practical consequences for biological ageing and muscle performance. Indeed, emerging evidence suggests that blood mDNAge inversely associates with grip strength and frailty in ageing humans (Peterson et al., 2022; Verschoor et al., 2021) and is lower following a dietary/physical activity intervention in postmenopausal women (Fiorito et al., 2021). Exercise training and OKSM share substantial gene expression overlap.…”
Section: Discussionmentioning
confidence: 99%
“…As our moderated-mediation results suggest, biological age-related declines in strength occurred in males and females suggesting that HGS could be used as a proxy measure of accelerated aging, providing that we acknowledge sex as a biological variable and consider this in methodological designs. Previous research examining strength performance as a standalone variable, however, has either provided no association with epigenetic aging ( McCrory et al, 2020 ), or demonstrated an association in females only ( Peterson et al, 2021 ). Previously, a stronger association between HGS and impaired activities of daily living has been observed in men than women ( Oksuzyan et al, 2010 ).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, evidence favors DNAmGrimAge estimates of biological aging as the most predictive “clock” for physical performance, whereby reductions in physical function are associated with an older epigenome ( Lu et al, 2019 ; McCrory et al, 2020 ; Peterson et al, 2022a ). However, the limited available data examining associations of epigenetic age specifically with HGS indicate no association ( McCrory et al, 2020 ), or an association in females only ( Peterson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…32 Grip strength dynamometers are easy to use, provide more precise measurement than the alternative manual muscle testing, and have established psychometric properties in nearly all conditions. 33,34 Two important features of these successful measurement RT are their adaptability to different populations and their relative advantage over prior gold standard measures of the vitals and strength domains. 31 Developers are likely to succeed by enhancing precision in current clinical metrics, instead of expending resources on the creation of novel measurement criteria.…”
Section: Rehabilitation Technology Characteristicsmentioning
confidence: 99%